Prolonged maintenance of human hair follicles in vitro in a serum-free medium - Westgate, G E; Gibson, W T; Kealey, T; Philpott, M P (British journal of dermatology (1951), 1993)
We have previously reported the in vitro growth of human hair follicles for up to 4 days in a partially defined medium containing serum. We now report the prolonged in vitro growth of isolated human hair follicles for at least 9 days. This was achieved after analysis of the contribution of certain components of the original medium and, by a process of elimination, deriving a completely defined medium supplemented only with antibiotics, L-glutamine, insulin and hydrocortisone. We have shown, by [methyl-3H] thymidine autoradiography, that the hair follicles grown in this medium maintain an in vivo pattern of DNA synthesis, and that the gross morphology and histology of these maintained hair follicles remains similar to that of freshly isolated hair follicles. We have also shown that the patterns of keratin synthesis, as determined by [35S] methionine labelling, do not alter with maintenance.